Fluorescent Probes of Biological Membranes - Waggoner, Alan S. (1970)
Fluorescent and phosphorescent probes that have readily interpretable emission properties can be specifically inserted into biological macromolecules to reveal facets of their structure and dynamics: (1) Proximity. Singlet-singlet and triplet-singlet energy transfer can serve as spectroscopic rulers in the 10-65 Å range, whereas triplet-triplet transfer can be used to show that two groups are less than about 12 Å apart. (2) Rotational mobility. Nanosecond fluorescence polarization measurements can reveal whether a macromolecular system has any modes of flexibility in times of nanoseconds. (3) Polarity. The presence of mobile dipoles in the environment of certain chromophores is reflected in their fluorescence quantum yield and emission spectrum. We have synthesized a number of new fluorescent probes for biological membranes. Anthroyl stearic acid (I), dansyl phosphatidyl ethanolamine (II), and octadecyl naphthylamine sulfonic acid (III) are readily incorporated into bilayer vesicles composed of phosphatidyl choline. The emission spectra of these probes in the vesicles indicate that the chromophore of I is located in the hydrocarbon region, that of II is located in the glycerol layer, and that of III is located at the aqueous interface of the bilayer. Thus, fluorescent chromophores can be selectively placed in different transverse regions of a model membrane system.